The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5194/acp-13-11235-2013
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal vertical distribution of the Saharan Air Layer and its modulation by the wind

Abstract: Abstract. The Saharan Air Layer (SAL) influences largescale environment from western Africa to eastern tropical Americas, by carrying large amounts of dust aerosols. However, the vertical distribution of the SAL is not well established due to a lack of systematic measurements away from the continents. This can be overcome by using the observations of the spaceborne lidar CALIOP onboard the satellite CALIPSO. By taking advantage of CALIOP's capability to distinguish dust aerosols from other types of aerosols th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 132 publications
10
116
0
3
Order By: Relevance
“…Systematic studies of the east-to-west dust transport with the satellite lidar CALIOP (Cloud and Aerosol Lidar with Orthogonal Polarization) were then presented by Liu et al (2008a, b). Further Saharan dust studies over the tropical Atlantic based on CALIOP measurements can be found in Adams et al (2012) and Tsamalis et al (2013). The latter authors characterized the decay of the Saharan dust amount in terms of layer descent and deposition velocity.…”
Section: Saltrace R/v Meteor Cruise and Instrumentationmentioning
confidence: 99%
“…Systematic studies of the east-to-west dust transport with the satellite lidar CALIOP (Cloud and Aerosol Lidar with Orthogonal Polarization) were then presented by Liu et al (2008a, b). Further Saharan dust studies over the tropical Atlantic based on CALIOP measurements can be found in Adams et al (2012) and Tsamalis et al (2013). The latter authors characterized the decay of the Saharan dust amount in terms of layer descent and deposition velocity.…”
Section: Saltrace R/v Meteor Cruise and Instrumentationmentioning
confidence: 99%
“…In boreal summer, SAL is characterized by hot, dry, very dust-laden air, and it is located between 10 and 25 • N (Dunion and Marron, 2008;Tsamalis et al, 2013). This SAL is marked by very strong potential temperatures up to 40 • C and a radon presence ( 222 radon) indicating the desert origin of air masses (Carlson and Prospero, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In winter, the SAL is characterized by the transport of dust containing chemical elements such as aluminum (Al), silicon (Si), iron (Fe), titanium (Ti), and manganese (Mn; e.g., Formenti et al, 2001;Ben-Ami et al, 2010) and is located between 5 and 10 • N (e.g., Tsamalis et al, 2013). Some studies relating aerosols to their transport are generally a simple description of the vertical distribution of aerosols in the SAL (Generoso et al, 2008;Liu et al, 2008;Ben-Ami et al, 2009;Braun, 2010;Yu et al, 2010;Adams et al, 2012;Ridley et al, 2012;Yang et al, 2012) or a description of the seasonality of the SAL in connection with large-scale dynamics (Liu et al, 2012;Tsamalis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the summer months, the westward moving SAL typically occurs 5 at relatively high altitudes (1-6km) in the Cabo Verde area (Tsamalis et al, 2013), and the warm, dry, dust-laden air creates a stable layer that is separated from the lower levels by a strong temperature inversion (Wong et al, 2009). …”
Section: Potential Source Areas and Transport Historymentioning
confidence: 99%